Comparative Experimental Study on Strength Properties of Red Clay Modified by Cement and Industrial Solid Waste Powder - Xianlong Lu; Qiang Yu; Jiayu Xu; Bing Yue; Mingqiang Sheng (Advances in Civil Engineering)
Because of the existence of clay minerals such as montmorillonite in red clay, the strength of red clay decreases significantly as water content increases. This study aims to improve the strength of red clay by using three different kinds of industrial solid waste powder, i.e., steel slag (SS) powder, fly ash (FA), and ground-granulated blast furnace slag (GGBS). At the same time, the ordinary Portland cement (OPC) was selected as a comparison of the improvement effect on the strength of red clay modified by the aforementioned industrial solid waste powder. The properties of the red clay and the industrial solid waste powder were documented comprehensively. The unconfined compressive strength (UCS) tests were conducted on the specimens of the red clay and the red clay modified by the OPC, SS, FA, and GGBS, which had been cured for 3, 7, and 21 days at a temperature of 25°C, respectively. The results showed that the strength of red clay can be significantly improved by the three kinds of industrial solid waste powder. After a 21-day curing period, the experimental results showed that the UCS of the red clay modified by 7% SS, 5% FA, and 5% GGBS increased by 252%, 131%, and 140% compared to that of the red clay without modification. However, the modification effects of the SS, FA, and GGBS on the red clay were generally inferior to that of the OPC. By observing the microstructures of the modified clay, the mechanism of industrial solid waste powder and cement improving the strength of the red clay was analyzed. The findings in this study can provide a reference for improving subgrade strength by a soil-modification method in road constructions.